Melatonin in the regulation of human life and its role in development pathology - A. V. Shilova; N. I. Ananyeva; N. Yu. Safonova; L. V. Lukina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The aim of our study was to research the literature data available for analysis of the melatonin role in the neurological and mental disorders origin. Materials and methods: to compile a literature review by keywords, articles there were selected and analyzed in the MEDLINE / PubMed and e-library databases from 1993 to 2021. For a detailed analysis, 42 literature sources were selected for the melatonin role in the development of neurological and mental disorders. Results: Melatonin is a hormone with unique adaptive capabilities. Violation of its production, both quantitatively and its rhythm, is the starting point, leading at the initial stages to desynchronizes, followed by the emergence of organic pathology. Consequently, the very fact of a violation of melatonin production can be the cause of various diseases. It was found that the volume of the pineal gland can change with the development of various types of neurological and psychiatric diseases, which is associated with a violation of the synthesis of melatonin and serotonin. Melatonin has been found to have important protective properties in Alzheimer’s disease—the ability to inhibit the formation of betaamyloid peptide in the brain, which is the morphological basis of this disease. The same correlation was found in patients with autism, psychosis and obsessive-compulsive disorder compared with healthy volunteers. Regarding the neuroprotective properties of melatonin, it should be noted its effectiveness in age-related diseases (Alzheimer’s, Parkinson’s, vascular diseases) Conclusion: Melatonin can be considered as a unique bioregulator, adaptogen and stabilizer of the whole organism and, in particular, the functions of the central nervous system. It has been proven that disruption of melatonin metabolism leads to various neurological and mental disorders.